Efficient inorganic perovskite solar cells made by drop-coating in ambient air. (February 2023) - Xiao, Hanrui; Zuo, Chuantian; Zhang, Lixiu; Zhang, Wenhua; Hao, Feng; Yi, Chenyi; Liu, Fangyang; Jin, Huile; Ding, Liming
Abstract: Inorganic perovskites are receiving growing attention due to good thermal stability and fast-improving photovoltaic performance. However, most of the high-efficiency inorganic perovskite solar cells (PSCs) were fabricated in inert atmosphere. Herein, we report an additive-assisted airflow drying (AAD) method to make mixed-halide inorganic perovskite films in ambient air. The nucleation and crystal growth during film formation are controlled by using airflow dying and lead acetate trihydrate additive, producing pinhole-free film with low defect density. Consequently, efficiency of CsPbI2.25 Br0.75 PSCs is improved to 18.49%, which is the highest for wide-bandgap (>1.8 eV) inorganic PSCs. An efficiency of 17.08% is achieved for PSCs made under moderate relative humidity (40–50%). Moreover, PCEs of 17.39% and 11.54% are achieved for CsPbI2 Br and CsPbIBr2 PSCs, respectively, which are among the best PCEs for CsPbI2 Br and CsPbIBr2 PSCs. This work provides a convenient and efficient method to make efficient inorganic PSCs in ambient air. Graphical Abstract: ga1 Highlights: A facile additive-assisted airflow drying method is developed to make inorganic perovskite films by drop-coating in air. CsPbI2.25 Br0.75 PSCs made in air give a PCE of 18.49%, which is the highest PCE for wide-bandgap (>1.8 eV) inorganic PSCs. PCEs of 17.39% and 11.54% are achieved for CsPbI2 Br and CsPbIBr2 solar cells, respectively. CsPbI2.25 Br0.75 solar cells with an effective area of 1 cm 2 delivered a PCE of 15.22%.